PERLINDUNGAN HUKUM ATAS KERUGIAN PRAKTIK INVESTASI ILEGAL DENGAN SKEMA PONZI - Wardiani, Gusti Ayu Deandra; Purwanti, Ni Putu (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 4 (2023), 2023)
Advances in technology create a new order of life in society. People become more creative by trying online to improve welfare. Along with this new pattern, many businesses have implemented Ponzi schemes in their business activities so that, of course, people are tempted by the offer of large profits in a short time from investment. This raises a problem where there is no legal regulation that regulates matters related to illegal investment practices with the Ponzi scheme which causes people to freely offer illegal investments with the Ponzi scheme. With this background, the writing of this journal is done to find out how the legal protection for the loss of illegal investment practices with the Ponzi scheme and the legal consequences of illegal investments with the Ponzi scheme. The method used in this paper is a normative legal research method using a conceptual legislation approach with legal material collection techniques and using primary, secondary, and tertiary legal materials as a source of legal material. The legal material analysis technique used is descriptive qualitative. The results of this study indicate that OJK has carried out various supervisions on illegal investments with the Ponzi scheme by establishing an investment alert task force and preventive and repressive strategies against illegal investments with the Ponzi scheme. However, the supervision carried out has not been able to handle illegal investment cases with the Ponzi scheme as a whole, because the term Ponzi scheme is not yet known and regulated in laws and regulations. OJK should be able to take concrete action by adding additional articles related to the prohibition of Ponzi schemes in Indonesia. The legal consequences of contracts and subjects of illegal investment agreements with the pinzi scheme are null and void.   Keywords: Legal Protection, Illegal Investment, Ponzi Scheme